2021
DOI: 10.3390/ani11092572
|View full text |Cite
|
Sign up to set email alerts
|

Methadone or Butorphanol as Pre-Anaesthetic Agents Combined with Romifidine in Horses Undergoing Elective Surgery: Qualitative Assessment of Sedation and Induction

Abstract: While butorphanol is the most commonly used opioid in horses, methadone is not licensed in most countries. Our aim was to compare the effects of both drugs, combined with romifidine, regarding the quality of sedation and induction in horses undergoing elective surgery. Results indicate the suitability of both methadone and butorphanol in this patient population. Animals were scored 10 min after intravenous injection of sedatives. Despite lower overall sedation (OS) score in horses receiving methadone (p = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In one study in healthy horses undergoing elective surgery, methadone was shown to enhance sedation from alpha‐2 adrenoceptor agonists. It has also been shown to decrease noise response while maintaining good postural stability 21 . However, the analgesic effects of methadone and its duration remain to be investigated in the equine population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study in healthy horses undergoing elective surgery, methadone was shown to enhance sedation from alpha‐2 adrenoceptor agonists. It has also been shown to decrease noise response while maintaining good postural stability 21 . However, the analgesic effects of methadone and its duration remain to be investigated in the equine population.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to decrease noise response while maintaining good postu-ral stability. 21 However, the analgesic effects of methadone and its duration remain to be investigated in the equine population.…”
Section: Discussionmentioning
confidence: 99%
“…24 While well-suited for assessing sedation depth in standing, undisturbed horses, these methods are not easily applied to sedated horses undergoing a potentially painful stimulus. Scoring systems have been described for assessing horse responses to various tactile, auditory, and visual stimuli 2,22,25,26 ; however, reviewerassigned scoring systems are inherently prone to subjectivity and scorer bias. Alternatively, automated analysis of animal behavior is widely utilized in biomedical research, and open-source availability of software code enables modification to perform the specific needs of a particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Butorphanol, morphine, methadone and hydromorphone are commonly used in equine analgesia and their pharmacokinetics and pharmacodynamics have been thoroughly investigated ( 2 , 24 , 29 , 30 , 32 , 33 ). Butorphanol, a synthetic strong κ -opioid receptor agonist and weak μ -opioid receptor antagonist ( 2 , 34 38 ), has been observed to induce a transient reduction in gastrointestinal motility in anesthetized horses when used as CRI at a dosage of 13 μg/kg/h ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a widely recognized side effect of opioid treatment in all species, affecting up to 95% of human patients, attributed to diminished coordinated motility, prolonged transit time, enhanced fluid absorption from intestinal contents and decreased secretion of fluids and electrolytes into the intestinal lumen (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). While opioids provide analgesia by stimulating μ-, κand δopioid receptors in the brain, the dorsal horn of the spinal cord and peripheral tissues, the activation of opioid receptors within the gastrointestinal tract can decrease motility and induce alterations in the secretion, absorption and transport of electrolytes and fluids (9,(11)(12)(13)(14)(15)(16)(17)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%